Comparative Evaluation of Rebound and Perkins Tonometers in Pediatric Glaucoma With Varied Corneal Characteristics. Issue 4 (April 2021) - Angmo, Dewang; Ramesh, Priyanka; Mahalingam, Karthikeyan; Azmira, Kishan; Pandey, Shivam; Gupta, Viney; Sihota, Ramanjit; Dada, Tanuj
Abstract : Precis: Icare tonometer overestimated intraocular pressure (IOP) as compared with Perkins and this variation was higher in IOP>19 mm Hg and corneal opacity in patients with pediatric glaucoma. Purpose: To compare the IOP measured by Icare ic200 with Perkins tonometer in pediatric glaucoma with different corneal characteristics. Methods: Patients of pediatric glaucoma posted for routine examination under anesthesia, age below 12 years were enrolled. All patients underwent IOP measurement with Perkins and Icare ic200 tonometer by the same observer. Basic demographic data and other relevant clinical data were recorded. Central corneal thickness (CCT), horizontal corneal diameter, and corneal characteristics such as cornea clarity was recorded. Results: A total of 194 eyes of 105 patients were analyzed. The difference between Perkins and Icare IOP was −0.816 mm Hg with the Bland-Altman plot 95% limits of agreement (LoA) from −11.194 to 9.562 mm Hg and 5.1% (10) values lying outside LoA. At IOP <19 mm Hg, the difference was −0.65 mm Hg and IOP ≥19 mm Hg, the difference was higher, −1.12 mm Hg. In the clear cornea group (123 eyes), the difference in IOP by 2 tonometers was −0.776 mm Hg with the Bland-Altman plot 95% LoA between −10.679 and 9.128 mm Hg. In hazy corneas (36 eyes), the difference in IOP was 0.531 mm Hg. The Bland-Altman plot showed 95% LoA between −6.242 and 7.303 mm Hg. In the scarred cornea group (35 eyes), the difference in IOP between the 2 was −2.343 mm Hg and the Bland-Altman plot showed wide 95% LoA from −16.302 to 11.616 mm Hg. Conclusion: Icare tonometer overestimated IOP as compared with Perkins and this variation was higher in eyes with IOP≥19 mm Hg, CCT >615 μm, and scarred corneas. A moderate correlation between IOP and CCT for both tonometers was noted.